Introduction - Editor-in-Chief (Thai Journal of Rheumatology, 2024)
Welcome to the second issue of the Thai Journal of Rheumatology. This journal aims to disseminate important information and research in the field of rheumatology, focusing on providing knowledge to doctors and medical personnel involved in the care and treatment of patients with rheumatic diseases. In this issue, we have an intriguing original article on the nutritional status of patients with systemic sclerosis, and a literature review on practical approaches to managing autoimmune disease-related interstitial lung disease. Additionally, there is a case report on antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis in tuberculosis patients, and clinical images testing medical knowledge about physical examinations. We also feature a significant case study on scleroderma renal crisis. We hope this issue will be beneficial and serve as a valuable resource for everyone interested and working in the field of rheumatology.